Pelatihan Pembuatan Laporan Keuangan Berbasis Digital Menggunakan Aplikasi Kas pada Santri Pesantren Riyadul Hidayah RH La Tahzan Cinangka, Depok. - Hunein, Hamida; Fitrianti, Dini; Wizanasari (Abdimisi, 2025)
This community service program entitled "Training on Digital-Based Financial Report Preparation Using the KAS Application for Students of Riyadul Hidayah (RH) Islamic Boarding School – La Tahzan, Cinangka, Depok" aims to enhance participants' skills in preparing financial reports through a free, web-based application. The training was conducted on March 20–21, 2025, at Pesantren Tahfidz La Tahzan, Cinangka, Sawangan, Depok, and involved 25 students. The activity began with theoretical sessions on digital financial administration, followed by hands-on practice in operating the KAS web application, facilitated by lecturers from the Accounting Study Program at Universitas Pamulang. The expected outcomes of this program include: (1) participants’ ability to identify and understand web-based applications; (2) proficiency in using the KAS School financial application; (3) comprehension of digital-based cash report management; and (4) application of the acquired skills in financial administration practices within the pesantren. Keywords: Digital Financial Report, KAS Application, Web-Based Administration